Gakkel Ridge basalt melt inclusion and mineral chemistry ... - Shaw, Allison (Interdisciplinary Earth Data Alliance (IEDA), 2011)
Analyses of volatile, major, and trace elements for a suite of glasses and melt inclusions from the 85 degrees E segment of the ultra-slow spreading Gakkel Ridge. ... : Shaw, A. M., M. D. Behn, et al. (2010). "Deep pooling of low degree melts and volatile fluxes at the 85 degrees E segment of the Gakkel Ridge: Evidence from olivine-hosted melt inclusions and glasses." Earth and Planetary Science Letters 289(3-4): 311-322. ...